ISLAM, ETHNICITY AND THE STATE: Identity Politics in Malaysian Public Policy - Pakpahan, Saiman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research analyzes identity politics in religion-based public policy in Malaysia as a case study in Southeast Asia. Using Fairclough's critical discourse analysis approach, this research explores how Malay-Islam is hegemonically positioned in the constitution and state practice through institutions such as Jabatan Kemajuan Islam Malaysia (JAKIM) and the dual justice system. The findings show that this dominant discourse influences various sectors of public policy, especially education and law, which has implications for discrimination against non-Muslim minorities. The study also identifies the emergence of counter-discourses from civil society organizations that fight for pluralism and justice, although they are often silenced through recontextualization strategies by the state. This research contributes to the understanding of how identity politics operates in multicultural and multi-religious contexts, and its implications for public policy in the Southeast Asian region.